Evaluasi Instalasi Pengolahan Air Limbah (IPAL) Domestik Pada Unit Pengolahan Biologis Terhadap Parameter BOD Di Industri Pakan Ternak Surabaya - Sekar Huwaidah Qatrunada; Mohamad Mirwan; Muhammad Firdaus Kamal; Andrea Thrisiawan Pradhana (Jurnal Teknik Mesin, Industri, Elektro dan Informatika, 2024)
Domestic wastewater can be sourced from industrial activities, one of which is the Feedmill Industry. The Surabaya Feedmill Industry has been treating domestic wastewater using a WWTP. The management of domestic wastewater is based on the Technical Approval (PERTEK) of Wastewater Utilization for Application to Land. Based on the results, there are parameters that do not fulfill the quality standards. The parameter is Biological Oxygen Demand (BOD), an evaluation is needed to enhanced WWTP performance. The purpose of this research is calculating the percent removal of BOD, COD and TSS parameters in the biological treatment unit and identifying factors that can affect the removal of BOD parameters in the existing conditions of the biological treatment unit in the Surabaya Feedmill Industry. The method used is a literature study using the Ludwig Sasse equation. In the calculation of the average water discharge of 5.93 m³/day, only 29.6% of the planned discharge. The results of the calculation of HRT in biological unit processing have not met the design criteria, except for the aerobic biofilter. The BOD/COD ratio is 0.33. According to the existing calculation, the final result for the BOD parameter is 5.11 mg/L, COD is 24.38 mg/L and TSS is 37.33 mg/L. The design air requirement is 27.64 m³/day. Other factors that affect BOD removal are Dissolved Oxygen (DO) levels in the Aerobic Biofilter, nutrient requirements, and Food to Microorganism (F/M).